2021
DOI: 10.1097/gox.0000000000003742
|View full text |Cite
|
Sign up to set email alerts
|

Operational and Financial Impact of COVID-19: A Survey of Plastic Surgeons in Miami

Abstract: Background: In response to the COVID-19 pandemic, new guidelines were issued cautioning against performing elective procedures. We aimed to assess the impact of the COVID-19 pandemic on operational and financial aspects of plastic surgery in Miami. Methods: A multiple-choice and short-answer survey regarding practice changes and financial impact was sent to all 67 members of the Miami Society of Plastic Surgeons. Results: A 41.8% (n = 28) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…As a result, unsurprisingly, plastic surgeons across the board have seen fewer patients and performed fewer surgeries in the months immediately following the COVID-19 pandemic [3]. This substantial drop in patient access coupled with continued financial overhead carried by many practicing plastic surgeons has had a significant impact on the financial stability of plastic surgery practices [4] Several policies have been enacted to help prevent collapse of the healthcare system, including several physician-specific grants and loans developed to keep small businesses afloat as they continue to navigate through economic hardships [3]. While the operational and financial impacts of COVID-19 on the healthcare system are evident, the impact of the pandemic on physician relationships with industry and their subsequent financial implications has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, unsurprisingly, plastic surgeons across the board have seen fewer patients and performed fewer surgeries in the months immediately following the COVID-19 pandemic [3]. This substantial drop in patient access coupled with continued financial overhead carried by many practicing plastic surgeons has had a significant impact on the financial stability of plastic surgery practices [4] Several policies have been enacted to help prevent collapse of the healthcare system, including several physician-specific grants and loans developed to keep small businesses afloat as they continue to navigate through economic hardships [3]. While the operational and financial impacts of COVID-19 on the healthcare system are evident, the impact of the pandemic on physician relationships with industry and their subsequent financial implications has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the pandemic, several studies reporting the impact of COVID-19 on plastic surgery have been published. These studies all showed a significant decline in the number of surgeries in both academic and private practice and, to a greater extent, in private practice [5][6][7][8]. As the number of cases began to decline, restrictions on elective surgeries began to decrease.…”
Section: Introductionmentioning
confidence: 98%